Cult television - Gwenllian-Jones, Sara; Pearson, Roberta E. (University of Minnesota Press, 2004)
Leading scholars examine such shows as The X-Files; Star Trek; Xena, Warrior Princess; and Buffy the Vampire Slayer to determine the defining characteristics of cult television and map the contours of this phenomenon within the scope of popular culture.